Chemically stable urea based COF for size selective heterogeneous catalysis - Basu, Arghya; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: chemical stability; Covalent organic framework; heterogeneous catalysis

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching

Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane

Unlocking the potential of proton conductivity in guanidinium-based ionic covalent organic nanosheets (iCONs) through pore interior functionalization - Kumar, Sushil; Hu, Jiahui; Pandikassala, Ajmal; Kurungot, Sreekumar; Addicoat, Matthew A.; Szekely, Gyorgy (Applied Materials Today, 2023)
Recently, scientists have been exploring the incorporation of proton carriers such as water and phosphoric acid (PA) into the pores and channels of porous materials to enhance proton conduction performance. Ionic covalent organic nanosheets (iCONs) have been identified as promising functional materials due to their inbuilt ionic interfaces, which can facilitate strong interaction with counter ions present inside the pore structure and thus shorten ion transport pathways. However, there is a lack of research related to proton conductivity in iCONs loaded with PA. To address this, we prepared three functionalized guanidinium-based iCONs using a solvothermal condensation reaction between guanidinium amine (TG) and functionalized terephthaldehyde (Da, Dha, and Dma). PA was also incorporated into the iCON structure via ex situ loading to observe its effects on proton conduction performance. The results showed that both the iCONs and PA-iCONs were highly stable in water, organic solvents, acidic and basic media. Amongst these PA-iCONs, one with hydroxyl-functionalization (PA-DhaTG) displayed high proton conductivity at 90 degrees C and 95% relative humidity due to a Grotthuss mechanism for protons. These functionalized guanidinium-based iCONs could prove useful for applications in energy conversion devices.
Keywords: chemical stability; Functionalized pore interior; Guanidinium group; ionic covalent organic nanosheets; proton conductivity